Fabrication of glass foams from industrial wastes used as insulating board - K. Pawanawichian (2018)
Insulating glass foam (IGF) was successfully fabricated by wet process. The starting proportion of 65 wt% waste glass, 12 wt% slag, 23 wt% commercial soap was added with 15 wt% Na 2 SiO 3 and represented then was sintered at 725 °C. The IGF had cellular structure with the macro-pore size at 0.428 mm and thin cell walls. Density, thermal conductivity and compressive strength were 0.310 g/cm 3 , 0.130 W/m.K and 0.78 MPa, respectively. The average pore diameter and porosity increased with increasing the Na 2 SiO 3 concentration and the sintering temperature. On the other hand, the density, thermal conductivity and compressive strength were decreased. © (2013) Trans Tech Publications, Switzerland.